Flagellimonas baculiformis sp. nov. and Flagellimonas crocea sp. nov., isolated from surface seawater of the Pacific Ocean - Wang, Ming-Lei; Fu, Ge-Yi; Xu, Xue-Wei (International journal of systematic and evolutionary microbiology, 2024)
Two Gram-negative, non-spore-forming, non-motile, non-flagellated bacteria, designated strains D6 and DH64 , were isolated from surface water of the Pacific Ocean. For strain D6 , growth occurred at 10-40 °C, pH 5.5-9.0 and in the presence of 0-8.0 % NaCl (w/v). For strain DH64 , growth occurred at 10-40 °C, pH 5.5-8.5 and in the presence of 0.5-8.0 % NaCl (w/v). Phylogenetic analysis based on 16S rRNA gene sequences indicated that strains D6 and DH64 both belonged to the genera , with the highest sequence identities to JCM 17757 (98.2 %) and JCM 11811 (98.6 %), respectively. The 16S rRNA gene sequence identity between strains D6 and DH64 was 95.9 %. The average amino acid identity and digital DNA-DNA hybridization values between the two strains and the nearest phylogenetic neighbours were 66.7-93.3 % and 16.1-38.5 %, respectively. The major respiratory quinone of both strains was menaquinone-6. The major polar lipid was phosphatidylethanolamine. The major fatty acids were identified similarly as iso-C G, iso-C and iso-C 3-OH. The genomic G+C contents of strains D6 and DH64 were determined to be 45.5 and 42.6 mol%, respectively. The combined genotypic and phenotypic data show that the strains represent two novel species within genera , for which the names sp. nov. and sp. nov. are proposed, with type strains D6 (=MCCC M28982 =KCTC 92604 ) and DH64 (=MCCC M28986 =KCTC 92975 ).